The effect of by catch fish additionin cassava (manihot esculenta crant) nugget preparation on consumer acceptance - Simarmata, Okto Oloan F; ', Suparmi; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was intended to evaluate the consumer acceptance on cassava nugget was added with trash fish meat. Trash fish consist of Rastrelliger sp, Epinephelus bleekeri, Engraulidae and Eleutheronema tetradactylum. Those fish was taken from fishermen in Sibolga. The fish was eviscerated and minced. Four types of nugget were prepared from a mixture of cassava 45,10%,tapioca flour 6,76 %, egg 45,10 %, msg (Monosodium glutamate) 0,23 %, white onion 1,35 %, salt 1,01 %, sugar 0,45 % and each types of the nugget was added with fish meat at a level of 0%, 10%, 20% and 30%. The nugget was evaluated for consumer acceptance. The nugget added with 30% fish meat was the most preferable. Moisture, protein and bacterial count of the nugget was 47,03%, 11,76%, and 4,1 respectively.Keywords: Cassava, by catch fish, consumer acceptance.